Relationship Between the Role of Parents and the Social Character of Preschoolers in Cahaya Kasih Christian Kindergarten in Keay Village and Recovery Christian Kindergarten 2 in Jengan Danum Village - Serafina Supiah (Rifa'Institute, 2023)
Introduction: The Preschoolers period is a golden period in the process of child development, meaning that it is a golden period for all aspects of human development, one of which is the development of children's socializing characters, therefore it is necessary for the role of parents to teach their children from an early age so that they can learn to interact with others. Objective: To determine the relationship between the role of parents and the social character of preschoolers in Cahaya Kasih Christian Kindergarten in Keay Village and Recovery Christian Kindergarten 2 in Jengan Danum Village. Methods: The research design in this study was descriptive correlation using a cross-sectional approach. The study was carried out in April 2022. Results and Discussion: The role of parents in the very good category (93.4%). The children's social character is in the good category (86.8%). Statistical test of the relationship between the role of parents and the social character of preschoolers pValue = 0.00 <0.05. Conclusion: There is a relationship between the role of parents and the social character of preschoolers in Cahaya Kasih Christian Kindergarten in Keay Village and Recovery Christian Kindergarten 2 in Jengan Danum Village.